Energy Drink-Associated Electrophysiological and Ischemic Abnormalities: A Narrative Review - Cao, Diana X.; Maiton, Kimberly; Nasir, Javed M.; Estes, N. A. Mark; Shah, Sachin A. (Frontiers in Cardiovascular Medicine, 2021)
An increasing number of cardiovascular adverse effects, emergency room visits, and deaths have been linked to energy drinks. In this review, we summarized available published literature assessing electrophysiological and ischemic adverse effects associated with energy drink consumption. Overall, 32 case reports and 19 clinical trials are included in this review. Ventricular arrhythmia, supraventricular arrhythmia, and myocardial ischemia were amongst the most commonly reported in case reports with 3 having a fatal outcome. Although serious ischemic changes, arrhythmias, or death were not observed in clinical trials, significant electrophysiological changes, such as PR/PQ interval shortening/prolongation, QT/QTc shortening/prolongation, and ST-T changes, were noted. QT/QTc interval prolongation appears to be the most significant finding in clinical trials, and there appears to be a dose-response relationship between energy drink consumption and QTc prolongation. The exact mechanisms and the particular combination of ingredients behind energy drink-induced cardiac abnormalities require further evaluation. Until more information is available, energy drink use should be considered as part of the differential diagnosis in appropriate patients presenting with electrocardiographic changes. Further, certain patient populations should exercise caution and limit their energy drink consumption.